Iron considerations for the athlete: a narrative review - Sim, M.; Garvican-Lewis, L. A.; Cox, G. R.; Govus, A.; McKay, A. K.; Stellingwerff, T.; Peeling, P. (European Journal of Applied Physiology, 2019)
Iron plays a significant role in the body, and is specifically important to athletes, since it is a dominant feature in processes such as oxygen transport and energy metabolism. Despite its importance, athlete populations, especially females and endurance athletes, are commonly diagnosed with iron deficiency, suggesting an association between sport performance and iron regulation. Although iron deficiency is most common in female athletes (~ 15-35% athlete cohorts deficient), approximately 5-11% of male athlete cohorts also present with this issue. Furthermore, interest has grown in the mechanisms that influence iron absorption in athletes over the last decade, with the link between iron regulation and exercise becoming a research focus. Specifically, exercise-induced increases in the master iron regulatory hormone, hepcidin, has been highlighted as a contributing factor towards altered iron metabolism in athletes. To date, a plethora of research has been conducted, including investigation into the impact that sex hormones, diet (e.g. macronutrient manipulation), training and environmental stress (e.g. hypoxia due to altitude training) have on an athlete`s iron status, with numerous recommendations proposed for consideration. This review summarises the current state of research with respect to the aforementioned factors, drawing conclusions and recommendations for future work.